2020
DOI: 10.1177/2059436420924947
|View full text |Cite
|
Sign up to set email alerts
|

Framing international news in China: An analysis of trans-edited news in Chinese newspapers

Abstract: This research explores the variations between Chinese party and non-party newspapers in the framing of trans-edited international news. Existing studies on the framing of Chinese domestic news show that the variations depend on the sensitivity of news, which invokes government control. However, it is not clear how strictly the government would control international news and whether party and non-party news organizations would show similarities or variations in the framing of it. To address these issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In fact, the Chinese government has a long tradition of selectively paraphrasing foreign news to foster party propaganda (Rudolph 1984), and separately reporting foreign and domestic responses to public emergencies (Jin Li, Brewer, and Ley 2017). However, even though the party outlets are obligated to advance party ideologies, the media framing of trans-edited international news seems largely factual (Kuang and Wang 2020;Kuang and Wei 2018). This factual framing of the information, I argue, serves to cultivate a sense of professionality and objectivity, which increases the credibility of the party's stand on the issue.…”
Section: Theory and Hypothesismentioning
confidence: 96%
“…In fact, the Chinese government has a long tradition of selectively paraphrasing foreign news to foster party propaganda (Rudolph 1984), and separately reporting foreign and domestic responses to public emergencies (Jin Li, Brewer, and Ley 2017). However, even though the party outlets are obligated to advance party ideologies, the media framing of trans-edited international news seems largely factual (Kuang and Wang 2020;Kuang and Wei 2018). This factual framing of the information, I argue, serves to cultivate a sense of professionality and objectivity, which increases the credibility of the party's stand on the issue.…”
Section: Theory and Hypothesismentioning
confidence: 96%
“…In reporting domestic issues, the Chinese press avoids themes threatening state legitimacy (e.g., responsibility or conflict frames). In contrast, in reporting international problems, it is acceptable to cover more controversial issues (Kuang and Wang 2020). It has also been demonstrated that Chinese elites use foreign news reporting to demonstrate other countries' flaws, highlight the PRC's relative advantages, and rebuff criticism of the Chinese government.…”
Section: Foreign News Reporting and Chinese Mediamentioning
confidence: 99%
“…Although some Chinese media outlets are privately owned, the Central Propaganda Department of the CCP censors all Chinese media (Luo 2015). Commercial news organisations have more freedom than party-sponsored media and have room for manoeuvre when covering international news (Kuang and Wang 2020). Still, discourse on sensitive topics is monitored to construct and spread narratives approved by the CCP.…”
Section: Foreign News Reporting and Chinese Mediamentioning
confidence: 99%
“…However, it cannot be denied that a limited number of journalists pursue professional journalism adopted by Western journalists (Wang & Lyu, 2022). Non-party newspapers are more likely to be receptive to the needs of the market than serving as the party's media mouthpieces (Kuang & Wang, 2020).…”
Section: The Chinese Media and The China Dailymentioning
confidence: 99%